Efficacy and Safety of Sofosbuvir-Based Direct-Acting Antiviral Agents Treatment for Patients with Genotype 3/6 Hepatitis C Virus Infection - Mei, Yong-yu (Can J Gastroenterol Hepatol, 2020)
AIMS: The aim is to evaluate the efficacy and safety of Sofosbuvir- (SOF-) based direct-acting antiviral agents (DAAs) treatment for patients with genotype (GT) 3/6 hepatitis C virus (HCV) infection. METHODS: Patients infected with GT 3/6 HCV and treated with SOF-based DAAs were enrolled in this prospective, open, single-center, and real-world study. Drugs included Sofosbuvir (SOF), Velpatasvir (VEL), Daclatasvir (DCV), and Ribavirin (RBV). The treatment regimens included SOF + RBV for 24 weeks, SOF + DCV ± RBV for 12/24 weeks, and SOF/VEL ± RBV for 12 weeks. RESULTS: A total of 54 patients were included. Age was 42.5 ± 10.4 years. Baseline HCV RNA was 6.29 ± 0.89log10 IU/mL. The numbers of GT 3a, 3b, and 6a patients were 10, 12, and 32, respectively. The numbers of chronic hepatitis, compensated cirrhosis, and decompensated cirrhosis patients were 39, 9, and 6, respectively. In patients with chronic hepatitis C and liver cirrhosis, sustained virological response 12 weeks after the end of treatment (SVR12) was 97.4% and 96.7%, respectively, and rapid virological response (RVR) was 75.0% and 57.1%, respectively. SVR12 of GT3a, GT3b, and GT6a was 100%, 83.3%, and 97%, respectively. ALT normality rate in chronic hepatitis group is higher than that in cirrhosis group at 4 weeks of treatment (89.7% versus 60.0%, p = 0.033) and at 12 weeks after EOT (94.9% versus 66.7%, p = 0.021). The overall incidence rate of adverse events was 44.4%, with fatigue being the most common (13.0%). CONCLUSION: SOF-based DAAs regimen can achieve ideal SVR12 for Chinese patients with both GT3a and GT6a HCV infection. The tolerance and safety of SOF-based DAAs regimen are good.